A pandemia da covid-19 no município de Salinópolis: uma análise a partir da modelagem matemática - SANTOS, Carla do Socorro da Silva (2024)
This work addresses the practice of Mathematical Modeling, conceived from the perspective of Mathematics Education in the context of the pandemic in 2020. Initially, we present some concepts of Mathematical Modeling, highlighting some considerations for the classroom and the Modeling perspective. This study features qualitative research, carried out with 3rd year high school students at a public school in Salinópolis – Pa. The general objective is to show, through mathematical modeling, the numbers of covid-19 in the year 2020 of health bulletins from the city of Salinópolis/Pa and question students about the usefulness of mathematics in the context of the pandemic. As a result, we brought interdisciplinary debates, of a social nature, in the areas of health, education, geography, biology and mathematics itself, seeking to analyze their contributions to the diagnosis, dissemination of the disease, the discovery of medicines and vaccines. It was also possible to understand that, through the context of the covid-19 pandemic, how mathematics acted through its mathematical models as structuring axes and what the roles of these models are in society, namely: informing through numbers, understanding the disease in a global and local context, understand the speed of contamination and deaths by day, month and year.